2011
DOI: 10.1093/bja/aer094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patient sex on general anaesthesia and recovery

Abstract: Patient sex is an independent factor influencing the response to anaesthesia and recovery after surgery. Women emerged faster from general anaesthesia but their overall quality of recovery was poorer. Female sex hormones, particularly progesterone, might be involved, with premenopausal women having faster recovery time but poor overall recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 39 publications
(22 reference statements)
8
101
1
4
Order By: Relevance
“…3,9,15 There was no correlation between age and PQR, which is consistent with other studies. 9 This finding may be explained by the fact that elder patients tend to positively evaluate their health status and attribute less relevance to pain, nausea and vomiting.…”
Section: Discussionsupporting
confidence: 91%
“…3,9,15 There was no correlation between age and PQR, which is consistent with other studies. 9 This finding may be explained by the fact that elder patients tend to positively evaluate their health status and attribute less relevance to pain, nausea and vomiting.…”
Section: Discussionsupporting
confidence: 91%
“…Women emerged faster from general anaesthesia but their overall quality of recovery was poorer. Female sex hormones, particularly progesterone, might be involved, with premenopausal women having faster recovery time but poor overall recovery [20].…”
Section: Resultsmentioning
confidence: 99%
“…A study by Buchanan et al [13] found that with the same anesthetic protocol for general anesthesia women recovered earlier than men; however women felt more pain in the recovery room and stayed there for longer. Whitley et al [14] stated that this may be due to differences in the pharmacodynamics of women.…”
Section: Discussionmentioning
confidence: 99%